NAPAK TILAS DANG HYANG NIRATHA DI PULAU BALI - I Nyoman Suka Ardiyasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
The presence of temples in Bali cannot be separated by some central figures who inspired the temple. One of the great figures who contributed to discovering the Pura Kahyangan Jagat in Bali is Dang Hyang Niratha. Dang Hyang Nirarta has build a lot temple in his travels on the Island of the Gods. Some temples are similar to Rambut Siwa Temple, Uluwatu Temple, Ponjok Batu Temple, Sakenan Temple and other temples which are now Pura Dang Kahyangan and Sad Kahyangan. The temple as a place of worship for Hindus, is also not uncommon to get visits of local and international tourists. The attraction was due to the sacredness and beauty of the location that was established by Dang Hyang Nirartha. This is of course a tourist destination that offers spiritual attractions.